Student Perspectives on First Year Experience Initiatives Designed for Pre-service Teachers in their First Weeks of University Study - Larkin, Kevin; Rowan, Leonie; Garrick, Barbara; Beavis, Catherine (Journal of University Teaching and Learning Practice, 2016)
Universities throughout Australia are increasingly investing significant amounts of time and money in efforts to improve the quality of first year students’ experiences and, by extension, increase retention, performance and student satisfaction. This paper reports upon a pilot research project conducted at a Queensland university that investigates student understandings of, and reactions to, a range of initiatives put in place to enhance their “first year experience”. The research showed that students had mixed reactions to the initiatives put in place to support them and that staff played a vital role in terms of how students responded to various forms of institutional support. In analysing the results the paper demonstrates the need for ongoing research into how a diverse cohort of students make sense of the first year experience they are offered.